Cognitive Precursors of Reading: A Cross-Linguistic Perspective - Landerl, Karin; Castles, Anne; Parrila, Rauno (Scientific studies of reading, 2022)
In this paper, we survey current evidence on cognitive precursors of reading in different orthographies by reviewing studies with a cross-linguistic research design. Graphic symbol knowledge, phonological awareness, morphological awareness, and rapid automatized naming were found to be associated with reading acquisition in all orthographies investigated. However, apart from rapid naming, this association is mostly interactive, meaning that young children develop their symbol knowledge, and phonological and morphological awareness during reading development. Especially for phonological awareness, cross-linguistic evidence involving phonologically transparent orthographies, both alphabetic and non-alphabetic, suggests that it may be less of a hurdle than in the complex English orthography. Cross-linguistic research designs can be a useful methodological approach to test limits of reading theories that were initially developed for alphabetic orthographies.